The Evolution Of Philosophy In The Development Of Management Theory - Fatmasari Endayani; Dyah Arini R; Agung Winarno; Heri Pratikto (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to explore the influence of philosophy on the development and application of management theory in organizational practice. The research method uses a mixed-methods approach that combines quantitative analysis through surveys and qualitative analysis through in-depth interviews, as well as the use of secondary data from annual reports and academic publications. The results of the study indicate that managerial strategies based on philosophical principles have a significant positive impact on organizational performance and employee satisfaction. This study also found that adaptation and flexibility in the application of management theory are very important in facing technological changes and globalization. The implications of these findings include theoretical contributions to the development of management science and philosophy, practical recommendations for managers in implementing more effective managerial strategies, and policy suggestions for policy makers to support managerial education and training that focuses on philosophical aspects and employee welfare.